Including Legumes in Bermudagrass Pastures - J. L. Moyer; L. W. Lomas (Kansas Agricultural Experiment Station Research Reports, 2017)
Use of legumes in bermudagrass pastures did not affect summer cow gains in 2016. Forage availability was also similar where ladino clover was used in the Legume system compared with where Nitrogen (N) alone was used. Estimated forage crude protein (CP) was greater for the Legume than the Nitrogen system in early summer, but was similar by mid-summer.
Keywords: crimson clover; white clover